PENERAPAN PERMAINAN SIMULASI SEBAGAI TEKNIK BIMBINGAN KELOMPOK UNTUK MENINGKATKAN KEMAMPUAN MENYELESAIKAN KONFLIK DI SMK NEGERI 4 GOWA - H. BURHANUDDIN (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2022)
The purpose of this study was to describe the ability to resolve conflicts before being given a simulation exercise at SMK Negeri 4 Gowa. And to find out the description of the ability to resolve conflicts after being given fiber simulation exercises to determine the effect of applying simulation games as a group guidance technique in resolving conflicts at SMK Negeri 4 Gowa. The subjects of this study were 15 students who experienced conflict between class XI students. The procedure for this research is a sampling technique with data collection through questionnaires (questionnaires), observations on students who experience conflicts between students. Data analysis in this study used descriptive qualitative consisting of data processing, data analysis, and data presentation. The results of this study concluded that the ability to resolve conflicts of class XI students at SMK Negeri 4 Gowa before being treated in the form of simulation exercises was in the medium category and after being treated in the form of simulation exercises was in the High category. There is also a major influence on the application of simulation games as a group guidance technique to improve students' ability to resolve conflicts at SMK Negeri 4 Gowa. ABSTRAKTujuan penelitian ini adalah untuk mengetahui gambaran kemampuan menyelesaikan konflik sebelum diberi latihan simulasi di SMK Negeri 4 Gowa. Dan untuk mengetahui gambaran kemampuan menyelesaikan konflik sesudah diberi latihan simulasi serat untuk mengetahui pengaruh penerapan permainan simulasi sebagai teknik bimbingan kelompok dalam menyelesaikan konflik di SMK Negeri 4 Gowa. Subyek penelitian ini adalah siswa yang mengalami konflik antar siswa kelas XI sebanyak 15 orang siswa. Adapun prosedur penelitian ini adalah dengan teknik sampling dengan pengumpulan data melalui angket ( kousioner ), observasi pada siswa yang mengalami konflik antar siswa. Analisis data dalam penelitian ini menggunakan deskriptif kualitatif yang terdiri dari pengolahan data, telaah data, dan penyajian data. Hasil penelitian ini disimpulkan bahwa kemampuan menyelesaikan konflik siswa kelas XI di SMK Negeri 4 Gowa sebelum diberi perlakuan berupa latihan simulasi berada dalam kategori sedang dan setelah diberi perlakuan berupa latihan simulasi berada dalam kategori Tinggi. Juga terdapat pengaruh besar terhadap penerapan permainan simulasi sebagai teknik bimbingan kelompok untuk meningkatkan kemampuan siswa dalam menyelesaikan konflik di SMK Negeri 4 Gowa.